A systematic review and meta‐analysis of the efficacy of processing stages and interventions for controlling Campylobacter contamination during broiler chicken processing. Issue 1 (3rd November 2021) - Dogan, Onay B.; Aditya, Anand; Ortuzar, Juan; Clarke, Jennifer; Wang, Bing
Abstract: Systematic review and meta‐analysis were conducted to quantify the effects of processing stages and interventions on the prevalence and concentration of Campylobacter on broiler carcasses. To comprehensively capture relevant evidence, six databases were searched using the keywords " Campylobacter " and "broiler chicken." The literature search yielded 10, 450 unique citations, and after applying predetermined inclusion and exclusion criteria, 72 and 53 relevant citations were included in meta‐analyses for processing stages and interventions, respectively. As the two primary outcomes, log reduction and prevalence changes were estimated for each stage or intervention using a random‐effects meta‐analysis approach whenever possible. The outcome‐level quality assessment was conducted following the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach. The analysis revealed that scalding and chilling majorly reduces the prevalence and concentration of Campylobacter . Immersion chilling reduces the concentration regardless of chemical additives, but its effect on prevalence is not conclusive. The effects of carcass washing applications remain uncertain due to the inconsistency and imprecision of both outcomes. Defeathering and evisceration were identified as stages that can increase both prevalence and concentration. Both chemical and physical processing interventions provide limited efficacy in concentration and prevalence reduction. Major limitations of the review were inconsistency and imprecision at the outcome level and reporting issues and data gaps at the study level. The results are expected to inform quantitative microbial risk assessment model development and support evidence‐based decision‐making.